OpenAIRE - Building a collaborative Open Access infrastructure for European researchers - Rettberg, Najla; Schmidt, Birgit (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
This paper outlines the efforts of the OpenAIRE networking team to establish a Europe-wide open access initiative. OpenAIRE is an effort to realize the open access policies of the European Commission, and has built an infrastructure to support the widest possible dissemination of project results within a certain funding area, FP7. The purpose of the paper is to highlight how such a service can be established through the work of a successful network of European open access contacts and by effective communication with a range of stakeholders. The paper also outlines the flexible technical infrastructure and research activities within the project. Not without its challenges, the approach to tackling existing barriers, such as building repository interoperability, are explored. The paper also introduces the aims and initial activities of the continuation project, OpenAIREplus.